Metaphorising the Nigerian space : a critical stylistic study of Stephen Kekeghe’s Rumbling Sky - Maledo, Richard Oliseyenum; Emama, Emmanuel Ogheneakpobor (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper examines the metaphorical representation of the socio-political and religious space, Nigeria, in Stephen Kekeghe’s award-winning collection of poems, Rumbling Sky (2020). Contemporary Nigerian space has been plagued with social, political, and religious vices such as election malpractices, corruption, religious intolerance, cyberspace crime, farmers-herders clash, secessionist claims, kidnapping, killings, and terrorist activities, just to name a few. Writers from different genres of literature have captured these vices in their creative output and critics have remained committed to such writings. This paper examines several vices that ravage the Nigerian space which are reflected and represented in Stephen Kekeghe’s Rumbling Sky, poems that received accolade by the 2020 Association of Nigerian Authors. The analysis of poems, therefore, employs critical stylistics and applies the conceptual metaphor approach as its framework, adopting Naming and Describing as its critical stylistic textual-conceptual function. The findings reveal that Stephen Kekeghe’s Rumbling Sky might better be considered as an adequate representation and reflection of the contemporary Nigerian space in poetry. It further reveals that the ills of the political ruling class and the tacit connivance of the Nigerian presidency are responsible for the perpetuation of social, political, and religious vices.